Civil liability in illegal online loans - Rizka Syafriana (Lembaga Riset Mutiara Akbar, 2026)
The development of financial technology–based online lending services in Indonesia has been accompanied by the widespread emergence of illegal online loan providers operating without registration or supervision from the Financial Services Authority (Otoritas Jasa Keuangan/OJK). These illegal practices are characterized by high interest rates, short repayment periods, and weak consumer protection, leading to increased defaults and legal uncertainty for borrowers. This study aims to examine the role of the OJK in regulating and supervising online loan companies and to analyze the civil liability arising from credit agreements involving illegal online lending. This research employs normative legal research using statutory and conceptual approaches, with data obtained through library research of primary and secondary legal materials. The findings indicate that the OJK functions as a regulator and supervisor to ensure order, transparency, and consumer protection in the financial services sector. Credit agreements with unlicensed online loan companies may be canceled due to the absence of legal authorization; however, debtors remain obligated to return the borrowed funds, and default does not eliminate civil liability.